Primary mediastinal leiomyoma: a rare case report and literature review - Li, Chuan; Lin, Feng; Pu, Qiang; Liu, Lunxu (Journal of Thoracic Disease; Vol 10, No 2 (February 14, 2018): Journal of Thoracic Disease, 2018)
Primary mediastinal leiomyomas are extremely rare, its etiology unknown, and up to the present has only been described in a few cases in the English literature. In this case report, we describe a 3-year-old girl with asymptomatic left upper quadrant abdominal mass. Chest computed tomography demonstrated a giant solid mass in the anterior mediastinum, which extended to the right hemi-thorax and left upper quadrant abdomen. Fortunately, the girl underwent a complete surgical tumor resection. The definitive diagnosis was primary mediastinal leiomyoma. To our best knowledge, this is the second case report of primary mediastinal leiomyoma of child.